Game-based Paragogy in Virtual Learning Space: Mathematics World of Fun (WoF) - Liyana, Truna; Norhunaini, Mohd Shaipullah; Nurul Syuhada, Ismail; Farah Liyana, Azizan (2024)
Mathematics World of Fun (WoF) is a mathematics game-based assessment designed to create an exciting learning assessment for Centre for Pre-University Studies, UNIMAS students. WoF combines the Roblox game and some topics taught in the class. Roblox's popularity renders it an ideal medium for enriching education, offering interactive experiences that resonate with modern learners. This approach aligns with paragogy, a peer-driven learning model wherein students collaborate, share knowledge and collectively shape their educational journey. WoF harnesses the engaging nature of video games to deliver educational content, making learning enjoyable and immersive. In WoF, Roblox serves as a dynamic environment where educators craft engaging educational games and simulations, fostering experiential learning. By integrating curriculum into Roblox, WoF promotes diverse subjects in an enjoyable format, nurturing critical skills like problem-solving and collaboration. WoF also can be a platform for evaluating students' understanding and skills development. Moreover, WoF facilitates holistic assessments, evaluating students' comprehension, critical thinking, and creativity. This approach aligns with current educational trends, emphasizing a holistic evaluation of student performance beyond traditional tests. By embracing WoF, educators respond to contemporary demands for interactive, student-centric learning tools, enhancing education's effectiveness and relevance in today's dynamic landscape. Therefore, the idea of using the Roblox games concept enables students to be resilient in solving mathematical problems.